Methods of punishment in kindergarten institutions from the point of view of their teachers Field study in Benghazi (Albayan Scientific Journal, 2023)
The study aimed to identify the teachers' point of view towards the use of punishment in the kindergarten. The researcher conducted a set of procedures which included a comprehensive survey of the available kindergarten teachers. The study included 90 teachers. The researcher then prepared a questionnaire as a means of collecting data. (31) paragraphs divided into five axes (psychological, verbal, social, physical), and then we identified the alternatives that represent them for each paragraph according to the five-scale scale (always, often, sometimes, rare, Of the validity and consistency of the questionnaire, were distributed to the sample members. In order to analyze the data, the appropriate statistical methods were used for the study objectives. The results showed that there is a great consensus in the opinion of the teachers about the use of educational punishment, it may achieve a high level or for social, psychological and physical punishment. (67%) followed by verbal punishment (68%), followed by corporal punishment (66%), psychological and social methods The ratio is almost average from the point of view of teachers. Differences were also found in the teachers' opinions regarding the use of punishment due to educational and non-educational qualifications in favor of non-educators. While there are no differences in the views of teachers in the use of educational punishment, attributed to the years of experience.